Global variance term premia and intermediary risk appetite - Peter Van Tassel; Erik Vogt (Federal Reserve Bank of New York, 2016)
Sellers of variance swaps earn time-varying risk premia for their exposure to realized variance, the level of variance swap rates, and the slope of the variance swap curve. To measure risk premia, we estimate a dynamic term structure model that decomposes variance swap rates into expected variances and term premia. Empirically, we document a strong global factor structure in variance term premia across the U.S., U.K., Europe, and Japan. We further show that variance term premia are negatively correlated with the risk appetite of hedge funds, broker-dealers, and mutual funds. Our results support the hypothesis that financial intermediaries are marginal investors in the variance swap market.
Keywords: G12; G13; C58; 330; variance swap; variance risk premium; term structure; empirical asset pricing; volatility; financial intermediaries